Mahzani Fest UNIMA 2023: Qualitative Interview Study of Internal Evaluation, Event Image, Satisfaction and Behavioral Intentions in the Future - Opod, Chrisna Riane; Ombuh, Irvandi Waraney (PT FORMOSA CENDEKIA GLOBAL, 2023)
Mahzani Fest 2023 organized by Universitas Negeri Manado, the result of collaboration between the Student Executive Board and Creative Batamang, was successfully held on October 14 2023, at the UNIMA Rectorate Square. A qualitative interview study, with students as respondents, was carried out to determine the factors that shape the event image, level of satisfaction, as well as future behavioral intentions towards Mahzani Fest 2023. Through the research carried out, it is hoped that it can provide information – important information for the organizer, Universitas Negeri Manado, for the next Mahzani Fest event.